Bromine in the tropical troposphere and stratosphere as derived from balloon-borne BrO observations - M. Dorf (Atmospheric Chemistry and Physics, 2008)
The first tropospheric and stratospheric (4 to 33 km) BrO profile is presented for the inner tropics derived from balloon-borne DOAS (Differential Optical Absorption Spectroscopy) measurements. In combination with photochemical modelling, total stratospheric inorganic bromine (Bry) is deduced to be (21.5±2.5) ppt in 4.5-year-old air, probed in 2005. We derive a total contribution of (5.2±2.5) ppt from brominated very short-lived substances and inorganic product gases to stratospheric Bry Tropospheric BrO was found to be <1 ppt. Our results are compared to two 3-D CTM SLIMCAT model runs, which differ in the lifetime of the bromine source gases, affecting the vertical distribution of Bry in the lower stratosphere. Bromine source gas measurements performed 10 days earlier Laube et al., 2008, indicate a lower Bry of (17.5±0.4) ppt. Potential reasons for this discrepancy are discussed.